Stochastic Modelling of Big Data in Finance - Swishchuk , Anatoliy (Boca Raton : CRC Press/Taylor & Francis, 2023)
Stochastic Modelling of Big Data in Finance provides a rigorous overview and exploration of stochastic modelling of big data in finance (BDF). The book describes various stochastic models, including multivariate models, to deal with big data in finance. This includes data in high-frequency and algorithmic trading, specifically in limit order books (LOB), and shows how those models can be applied to different datasets to describe the dynamics of LOB, and to figure out which model is the best with respect to a specific data set. The results of the book may be used to also solve acquisition, liquidation and market making problems, and other optimization problems in finance.
Includes bibliography and index.
Keywords: Finance; Stochastic modeling; Quantitative; Hawkes processes; Big data